2008
DOI: 10.1021/bm701399m
|View full text |Cite
|
Sign up to set email alerts
|

Protein Release from Galactoglucomannan Hydrogels: Influence of Substitutions and Enzymatic Hydrolysis by β-Mannanase

Abstract: O-Acetyl-galactoglucomannan (AcGGM) is the major soft-wood hemicellulose. Structurally modified AcGGM and hydrogels of AcGGM were prepared. The degree of substitution (DS) of AcGGM was modified enzymatically with alpha-galactosidase, and chemically with an acrylate derivative, 2-hydroxyethylmethacrylate (HEMA). The hydrolysis of AcGGM with beta-mannanase was shown to increase with decreasing DS. AcGGM hydrogels were prepared from chemically modified AcGGM with varying DS of HEMA. Bovine serum albumin (BSA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 33 publications
2
26
0
1
Order By: Relevance
“…Figure 13 shows the cumulative release profiles as a function of release time for each BSA‐loaded hydrogel sample in PBS solution (pH 7.4, I = 0.2 M). It was found that there was a burst release at the initial stage, which was also observed in some other systems reported elsewhere 47, 72, 73. The BSA located near the hydrogel surface could be released rapidly from the hydrogel to the medium as soon as the sample was placed into the buffer solution.…”
Section: Resultssupporting
confidence: 81%
“…Figure 13 shows the cumulative release profiles as a function of release time for each BSA‐loaded hydrogel sample in PBS solution (pH 7.4, I = 0.2 M). It was found that there was a burst release at the initial stage, which was also observed in some other systems reported elsewhere 47, 72, 73. The BSA located near the hydrogel surface could be released rapidly from the hydrogel to the medium as soon as the sample was placed into the buffer solution.…”
Section: Resultssupporting
confidence: 81%
“…Polymers used in the development of CDDS can be chemically modified, and these modifications can influence the extent of enzymatic degradation. For example, Roos et al synthesized the acetyl derivative of guar gum (AcGGM) and used this polymer to make a hydrogel of bovine serum albumin (BSA) (46). They observed that the rate of hydrolysis for modified AcGGM by β-mannase was affected by its degree of substitution (DS).…”
Section: Colon-specific Biodegradable Delivery Systemsmentioning
confidence: 99%
“…In addition to use in wound management, gels based on xyloglucans have been explored as vehicles for controlled drug delivery (Miyazaki et al, 1998;Roos et al, 2008). Research has shown that alkenyl-functionalized galactogluocomannans could offer sustained delivery of incorporated substances mediated by diffusion and enzymatic hydrolysis.…”
Section: Applications Of Hemicellulosesmentioning
confidence: 99%